VOLLEYBALL SMASH SKILL TRAINING MODEL FOR BEGINNER ATHLETES - Agusdi; Hernawan; Yasep Setiakarmawijaya (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this research is to find out the training model using Volleyball smash skills for novice athletes. The method used is Research &Development with mixed methods research approach that combines qualitative and quantitative methods. The number of samples as many as 40 respondents. The steps of this study include: 1) preliminary study stage; 2) the planning stage of model development; and 3) the stage of validation, evaluation and revision of the model. Furthermore, conduct the following effectiveness tests: (1) Establish the research subject group (R); (2) Carrying out a pre-test of smash capability (Q1); (3) Give treatment to the research subjects by applying a training model smash volleyball in noviceathletes (P); (4) Carrying out post-test smash capability volleyball (Q2); (5) Look for the average pre-test and post-test scores and compare between them; (6) Look for differences between the two averages through statistical methods (t-test) to determine whether or not there is a significant influence on the use of the model. The conclusion of this study resulted in the final product in the form of an exercise model and was very effective and efficient to improve theskill smash of novice athletes.